Scada desing for a prototype couch parts - Velásquez Costa, José (2010)
The prototype performs a classification and distribution of parts according to color and type of material of the pieces. The classification is done by two sensors that depending on the object may or may not be activated depending of the type of piece. A programmable logic controller (PLC) has the function of automatically controlling the entire process through a program. This program allows the distribution of the parts to different ramps where they will be stored. The physical process may be initiated by pressing a button on the prototype, as well as through a button on a computer screen. The display shows not only buttons, you can see in real time what happens in the prototype parts selection.